MOU signed between UMP and Hassan II University of Casablanca - UMP, PNC (2018)
Morocco, 11th October - A Memorandum of Understanding (MoU) was signed between Universiti Malaysia Pahang (UMP) and Hassan II University of Casablanca (H2UC). The MOU outlined collaborations in research, academic and student exchange programmes, dual degree programme for undergraduates and postgraduates degree programmes. It would also pave the way for the establishment of smart partnerships in knowledge sharing.